Teaching Strategies in a Post-Pandemic Virtual Education (Docentes 2.0 Journal, 2025)
The world experienced a global health crisis caused by the SARS-COV-2 virus, which led governments to implement confinements to curb contagion. In this context, education had to adapt quickly to new ways of teaching, especially the virtual modality. This research aimed to analyze the virtual teaching strategies teachers implement to achieve meaningful learning and encourage active participation of their students. The research was based on a systematic methodological approach, adopting the pragmatic paradigm, with a mixed approach and a descriptive narrative design, bibliographic documentary type, and cross-sectional, covering studies conducted in the last five years through a systematic review and the PRISMA method. The search for information was carried out in Scielo, Scopus, and Dialnet, from which 19 relevant articles were selected, the results indicated that the greatest geographical concentration in research on virtual teaching strategies is in Spanish-speaking countries and the Scielo database, the peak of this research was reached in 2021, highlighting mainly the technological aspect, which implies the implementation of ICT. Finally, teachers adopted new methodologies, prioritizing the design of learning experiences and encouraging active participation, critical thinking, and student autonomy. The strategies implemented seek to ensure meaningful learning and prepare students with innovation, transformation, and key competencies to face the challenges of an increasingly digitalized world.
Keywords: Learning; teaching strategies; virtual teaching; virtual education; post-pandemic